Efficiency Wages and Effort: Are Hard Jobs Better? - Eric Strobl; Frank A. Walsh (Institute for the Study of Labor (IZA), 2003)
Efficiency wage theory predicts that the wage per unit of effort will be lower in intensively monitored sectors. This wage differential will increase in effort. Using employer-employee matched data from Ghana we provide evidence supporting this hypothesis.
Keywords: J41; 330; efficiency wages; monitoring; Effizienzlohn; Leistungskontrolle; Reallohn; Schätzung; Ghana